2011
DOI: 10.3109/08941939.2011.557469
|View full text |Cite
|
Sign up to set email alerts
|

Limited Efficacy of Early Enteral Nutrition in Patients after Total Gastrectomy

Abstract: Since there was no significant difference regarding either the postoperative recovery course or complications, the routine placement of a nasojejunal tube for EEN is unnecessary in elective total gastrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This meta-analysis included 14 studies comparing EN and PN in gastric cancer resections. There were 10 papers from China, 3 papers from Japan, and 1 paper from Korea: Li et al [36], Wang et al [37], Li et al [38], Chen et al [1], Liu et al [39], Li et al [40], Gao [41], Hongyi et al [42], Chen [43], Li et al [44], Nomura et al [45], Akashi et al [46], Kamei et al [47], and Kim et al [48] . Nine papers were randomized with n = 1437 participants, and 5 papers were retrospective studies with n = 421 participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This meta-analysis included 14 studies comparing EN and PN in gastric cancer resections. There were 10 papers from China, 3 papers from Japan, and 1 paper from Korea: Li et al [36], Wang et al [37], Li et al [38], Chen et al [1], Liu et al [39], Li et al [40], Gao [41], Hongyi et al [42], Chen [43], Li et al [44], Nomura et al [45], Akashi et al [46], Kamei et al [47], and Kim et al [48] . Nine papers were randomized with n = 1437 participants, and 5 papers were retrospective studies with n = 421 participants.…”
Section: Resultsmentioning
confidence: 99%
“…The levels of albumin on POD < 7 were reported in 6 studies [1, 36, 3840, 44], with ( n = 1210) 609 participants in EN and 601 in PN groups. Heterogeneity was significant among studies that reported on PODs < 7 ( χ 2 = 44.98, P < 0.00001, I 2 = 89%), and PODs ≥ 7 was reported from 7 studies [1, 36, 3840, 43, 44] ( χ 2 = 34.29, P < 0.00001, I 2 = 83%). Therefore, the random effect model was used to calculate the effect sizes for both periods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation